For telework, please dial 7: Qualitative study on the impacts of telework on the well-being of contact center employees during the COVID19 pandemic in Portugal - Reinaldo Sousa Santos; Sílvia dos Santos Pereira (Administrative Sciences, 2023)
The COVID-19 pandemic has made teleworking a widespread form of work for contact center workers in Portugal, who are already used to work processes supported by technological platforms and digital workflows, but with little adherence to remote work. Deepening knowledge about the impact of teleworking on well-being at work is a relevant issue in the context of organizational literature. We conducted 14 semi-structured interviews with contact center workers who work in a large Portuguese company that provides fixed and mobile communication services, as well as customer service platforms. The interviews took place in April and May 2022. All participants had already carried out their functions in person and telework, and they were able to assess how telework added or took away their well-being at work. With the application of thematic analysis, seven themes (the basis for the title "For Telework, Please Dial 7") emerged that characterize teleworking as being capable of reinforcing well-being at work: performance, relationship, money, workplace, technology, time, and family. These results contribute to the reinforcement of the growing literature on what contributes to increasing well-being at work, and alert leadership and organizational management are needed to properly configure telework to generate a positive dynamic that fulfils employees' expectations and reinforces the organization's sustainability.
Keywords: 350; telework; well-being at work; human resources management; contact center; COVID-19